Dynamic compressive response of wrapped carbon fibre composite corrugated cores - Liu, Tao; Turner, Paul (Elsevier, 2017)
The experimental study on the compressive response of the carbon fibre composite sandwich structures with corrugated cores is reported. The corrugated core was manufactured from unidirectional carbon fibre pre-impregnated lamina wrapped around destructible triangular prisms. Individual wrapped triangular composite cores of relative density are cut from the sandwich beams and tested under both quasi-static compression and dynamic compression at a strain rate up to 8200s-1 using an instrumented direct impact Kolsky bar experiment. Under quasi-static compressive test, as the cores were provided with no lateral confinement, the failure mechanism of the composite core was that of progressive unwrapping of cores due to matrix cracking at the joints of the core webs. Under the dynamic compressive tests, the composite cores demonstrated rate-dependent behaviour. The strain rate dependency was attributed to the suppression of the quasi-static “unwrapping” failure mechanism, and inertial stabilisation of the struts against buckling leading to an upper-bound failure mechanism of crushing of carbon fibre material within the struts.